Hubungan antara Komponen Health Belief Model dengan Perilaku Pencegahan Covid-19 pada Masyarakat - Putri Purnama; Mustiah Yulistiani (Faletehan Health Journal, 2022)
The global threat of Covid-19 emerged continously and the number of victims continued to grow; thus, it was highly important to increase knowledge and perceptions of community to form preventive behaviours from Covid-19 transmission. This research objective was to determine the correlation between health belief model components and preventive behaviors of covid-19 among the community of Langensari, Banjar, West Java. This study was analytical descriptive with a cross-sectional design. The respondents were the people of Langensari sub-district with the total size of 100 respondents who were taken by using purposive sampling technique. The data collection used a questionnaire distributed via google form. The results of chi-square test indicated the perceived susceptibility of 0.000, perceived severity of 0.005, perceived benefit of 0.000, perceived barriers of 0.860, cues to action of 0.000, self-efficacy of 0.000, and significance value p<0.05. There was a correlation among perceived susceptibility, perceived severity, perceived benefit, cues to action, self-efficacy and covid-19 preventive behaviors; nevertheless, there was no correlation between perceived barriers and covid-19 preventive behaviors (p>0.005). Of 6 health belief model components, self-efficacy had the highest correlation value and impacted on developing Covid-19 preventive behaviors, while the one that had no effect was perceived barriers.